2015
DOI: 10.1117/12.2085803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EUV resist performance using interference lithography

Abstract: Extreme ultraviolet lithography (EUVL) stands as the most promising solution for the fabrication of future technology nodes in the semiconductor industry. Nonetheless, the successful introduction of EUVL into the extremely competitive and stringent high-volume manufacturing (HVM) phase remains uncertain partly because of the still limiting performance of EUV resists below 16 nm half-pitch (HP) resolution. Particularly, there exists a trade-off relationship between resolution (half-pitch), sensitivity (dose) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…EUV-IL enabled the characterization and development of new EUV resist materials before commercial EUV exposure tools became available. EUV resist has been performed on the EUV-IL beamline at SLS [25] and on the XIL beamline at SSRF [26]. Line structures of new EUV resist material with HP of 12 nm have been fabricated at the EUV-IL beamline at SLS, as shown in Figure 12.…”
Section: Euv Photoresist Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…EUV-IL enabled the characterization and development of new EUV resist materials before commercial EUV exposure tools became available. EUV resist has been performed on the EUV-IL beamline at SLS [25] and on the XIL beamline at SSRF [26]. Line structures of new EUV resist material with HP of 12 nm have been fabricated at the EUV-IL beamline at SLS, as shown in Figure 12.…”
Section: Euv Photoresist Evaluationmentioning
confidence: 99%
“…The EUV resist test result, done by XIL-II at SLS (reproduced with permission from[25] ©(2015) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE)).…”
mentioning
confidence: 99%
“…Further increase in the resolution will severely test the capabilities of the beamline experimental setup, the characteristics of high resolution EUV photoresists [10], and the fabrication of high quality IL masks. In the first case, the effect of source extension and of mechanical vibrations plays a role in resolution improvement and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…At PSI, for instance, we have had the opportunity to test many state-of-the-art CARs from vendors from all around the world and several promising candidates that simultaneously meet sensitivity, LWR and EL high performance requirements for the 7 and 5 nm logic node (16 nm and 13 nm half-pitch HP, respectively) for HVM have been identified for further investigation [2][3][4]. Although several CARs have been additionally found to be excellent performing down to 13 nm HP and even well resolved down to 12 nm and 11 nm, it has been demonstrated that alternative material solutions for HVM performance for upcoming technology nodes are still needed [2][3][4]. For that reason, the performance of alternative resist platforms such as Sn-based metal organic resist from Inpria Corp. and a negative tone CAR molecular resist from Irresistible Materials have been previously investigated [5,6].…”
Section: Introductionmentioning
confidence: 99%